Physical modelling of salt structural deformation in the Tajik Basin: insights into the formation of complex fold-and-thrust structures - Yin Wei; Ji Zhifeng; Zhang Yiqiong; He Jinyou; Wang Xueke; Zhang Mingjun; Jiang Ren; Zheng Yue; Pan Ying (Frontiers in Earth Science)
The structure of the Tajik Basin is characterized by a series of NE-trending fold-thrust belts that share a common detachment layer composed of Upper Jurassic evaporite rocks. These fold-thrust structures, thrusting face to face, converge toward the Vakhsh Depression. Due to limitations of seismic and drilling data, the controlling factors of the formation of the fold-thrust belts in the Tajik Basin remain controversial. Taking the Tajik Basin as a geological prototype, structural physical simulation experiments were conducted to decipher the controlling factors of salt-related structure deformation. The experiment results indicate that the tectonic deformation of the strata above the Jurassic evaporite rocks in the Tajik Basin is mainly controlled by the detachment layer of the Upper Jurassic evaporite rocks. The early salt diapirs in the Upper Jurassic played a key role in the formation of the thrust belts. Additionally, tectonic stress near the mountain front was rapidly transmitted to the inner basin due to the load of the structural wedge. Based on the results of physical simulation experiments, we speculate that the tectonic deformation of the subsalt strata and the basement in the Tajik Basin is primarily controlled by a deep detachment layer. The deformation of the subsalt strata is relatively gentle, which is conducive to the formation of large-scale, broad and gentle anticlinal structures. The anticlinal structures of the subsalt strata can form effective traps due to the sealing effect of the Upper Jurassic evaporite layer, offering promising exploration potential.